Computed Tomography Fluoroscopy–Guided Versus Conventional Computed Tomography–Guided Lung Biopsy: A Systematic Review and Meta-analysis. Issue 4 (July 2020) - Fu, Yu-Fei; Li, Guang-Chao; Cao, Wei; Wang, Tao; Shi, Yi-Bing
Abstract : Purpose: This study aimed to compare the feasibility, safety, diagnostic accuracy, and radiation dose between computed tomography (CT) fluoroscopy (CTF)–guided and conventional CT (CCT)–guided lung biopsy. Methods: Relevant articles up until February 2020 were identified within the PubMed, Embase, and Cochrane Library databases. Diagnostic accuracy rate, pneumothorax, and pneumothorax requiring chest tube served as primary end points, with technical success, hemoptysis, operative time, and radiation dose serving as secondary end points. Pooled odds ratios (ORs) were calculated for the dichotomous variables. Pooled estimates of the mean difference (MD) were measured for the continuous variables. Results: This meta-analysis included 9 studies. Seven studies were retrospective, and 2 studies were randomized controlled trials. A total of 6998 patients underwent either CTF-guided (n = 3858) or CCT-guided (n = 3154) lung biopsy. The diagnostic accuracy rate was significantly higher in the CTF group compared with the CCT group (OR, 0.32; P < 0.00001). No significant differences were detected between the CTF and CCT groups in terms of incidence rates of pneumothorax (OR, 0.95; P = 0.84), rates of pneumothorax requiring chest tube insertion (OR, 0.95; P = 0.84), technical success rates (OR, 0.41; P = 0.15), incidence rates of hemoptysis (OR, 1.19; P = 0.61), operative time (MD, −4.38; P = 0.24), and radiation dose (MD, 158.60; P = 0.42). A publication bias was found for the end points of pneumothorax requiring chest tube insertion and operative time. Conclusions: Compared with CCT-guided lung biopsy, CTF-guided lung biopsy could yield a higher diagnostic accuracy with similar safety and radiation exposure.